2019
DOI: 10.1039/c8ra10462j
|View full text |Cite
|
Sign up to set email alerts
|

Sponge-like N-doped carbon materials with Co-based nanoparticles derived from biomass as highly efficient electrocatalysts for the oxygen reduction reaction in alkaline media

Abstract: Sponge-like N-doped carbon materials with Co-based nanoparticles derived from biomass as high efficient electrocatalysts for oxygen reduction reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Co/N-MC shows two peaks at 2θ values of 23.6°a nd 43.1°corresponding to graphite structure of carbon (002) and the metallic cobalt (111) respectively. 58,61 Ni/N-MC also shows two peaks at 2θ values of 23.4°and 43.5°and are assigned to the graphite structure of carbon (002) and metallic nickel (111) respectively. 70,71 Pt/N-MC shows the four peaks at 2θ values of 24.1°and 39.8°, 46.2°a nd 67°which correspond to graphite structure of carbon (002) and to the metallic platinum Pt(111), ( 200) and ( 220) respectively of fcc platinum structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co/N-MC shows two peaks at 2θ values of 23.6°a nd 43.1°corresponding to graphite structure of carbon (002) and the metallic cobalt (111) respectively. 58,61 Ni/N-MC also shows two peaks at 2θ values of 23.4°and 43.5°and are assigned to the graphite structure of carbon (002) and metallic nickel (111) respectively. 70,71 Pt/N-MC shows the four peaks at 2θ values of 24.1°and 39.8°, 46.2°a nd 67°which correspond to graphite structure of carbon (002) and to the metallic platinum Pt(111), ( 200) and ( 220) respectively of fcc platinum structure.…”
Section: Resultsmentioning
confidence: 99%
“…2,[57][58][59][60] The pyridinic N has a lone pair of electrons which adsorbs the oxygen molecule and feeble O-O bonding, and helps improving ORR kinetics by the edge plane exposure. 6,[59][60][61][62][63][64] The graphitic N has the lone pair electron and is partially donated to the π* antibonding orbitals of the carbon which makes the carbon negative and nitrogen positive which creates active sites for the ORR. 65,66 Karnan et al reported activated high surface area carbon derived from aloe vera shows high specific capacitance suitable for supercapacitor.…”
mentioning
confidence: 99%
“… 46 Pyridine-N and pyrrolic-N can provide p-electrons through an aromatic π system, thereby producing improved catalytic activity for carbon supports. 47 Fig. 5(c) shows two doublet Ru 3p XPS core-level spectra, corresponding to Ru 3p 3/2 and Ru 3p 1/2 .…”
Section: Resultsmentioning
confidence: 99%
“…Various transition metal oxides supported on biochars have also attracted attention as electrocatalysts for ORR in alkaline electrolytes, namely α-MnO 2 [171], CeO 2 [172], Ni-Co oxides [167], CoO [180], and LaMnO 3 [142]. For example, Pi et al obtained a CeO 2 -encapsulated N-doped biochar catalyst by two processes: in the first method, a metal accumulating plant (Iris sibirica L.) was pyrolyzed (900 • C, 2 h, N 2 atmosphere) after having extracted Ce cations from environment; the second strategy consisted of the plant carbonization (900 • C, 2 h, N 2 atmosphere) before the accumulation of Ce, followed by loading of CeO 2 NPs via sonication.…”
Section: Oxygen Reduction Reaction (Orr)mentioning
confidence: 99%